Self-Study of the MOOC English Pronunciation in a Global World: Metaphonetic Awareness and English Accent Variation - Marta Nowacka (Research in Language)
This paper reports on a study in which Polish first-year university students of English, self-studied the massive open and online course (henceforth MOOC) entitled “Pronunciation in a Global World” to gain some knowledge on the fundamentals of phonetics (the notion of comprehensibility, nativeness and identity; vowels, consonants and selected suprasegmentals) and English accent variation. Its two main goals are: firstly, to examine the MOOC’s impact on the participants’ understanding of basic phonetic concepts and, secondly, to obtain the users’ assessment of this MOOC’s attractiveness and usefulness. In general, the results do not give evidence for the positive influence of the MOOC course on the students’ meta-awareness of English phonetics, since there are statistically significant differences in only three of sixty-eight questions between the experimental and control group. Nevertheless, many informants regard the course as useful (72%) and attractive (49%). Although the results do not support the hypothesis of the MOOC’s beneficial role in facilitating the understanding of English phonetics our stand is that this online training could complement classroom teaching as a form of blended learning.